Anomalous ion effects on rupture and lifetime of aqueous foam films formed from monovalent salt solutions up to saturation concentration - Karakashev, Stoyan I (Langmuir : the ACS journal of surfaces and colloids, 2008)
We report the effects of ions on rupture and lifetime of aqueous foam films formed from sodium chloride (NaCl), lithium chloride (LiCl), sodium acetate (NaAc), and sodium chlorate (NaClO 3) using microinterferometry. In the case of NaCl and LiCl, the foam films prepared from the salt solutions below 0.1 M were unstable they thinned until rupturing. The film lifetime measured from the first interferogram (appearing at a film thickness on the order of 500 nm) until the film rupture was only a second or so. However, relatively long lasting and nondraining films prepared from salt solutions above 0.1 M were observed. The film lifetime was significantly longer by 1 to 2 orders of magnitude, i.e., from 10 to 100 s. Importantly, both the film lifetime and the (average) thickness of the nondraining films increased with increasing salt concentration. This effect has not been observed with foam films stabilized by surfactants. The film lifetime and thickness also increased with increasing film radius. The films exhibited significant surface corrugations. The films with large radii often contained standing dimples. There was a critical film radius below which the films thinned until rupturing. In the cases of NaAc and NaClO 3, the films were unstable at all radii and salt concentrations they thinned until rupturing, ruling out the effect of solution viscosity on stabilizing the films